2020
DOI: 10.1111/jnc.15118
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of novel Cell Division Cycle Kinase 7 inhibitors on TDP‐43‐related pathogenesis such as Frontotemporal Lobar Degeneration (FTLD) and amyotrophic lateral sclerosis (ALS)

Abstract: TDP‐43 has been identified as the major component of protein aggregates found in affected neurons in FTLD‐TDP and amyotrophic lateral sclerosis (ALS) patients. TDP‐43 is hyperphosphorylated, ubiquitinated, and cleaved in the C‐terminus. CDC‐7 was reported to phosphorylate TDP‐43. There are no effective treatments for either FTLD‐TDP or ALS, being a pressing need for the search of new therapies. We hypothesized that modulating CDC‐7 activity with small molecules that are able to interfere with TDP‐43 phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…The observed control of microgliosis and subsequently, the neuroinflammation, together with the significantly prolonged survival of the animals, supported the evaluation of its efficacy in ALS patients (Trias et al, 2016). Moreover, it has been reported that the pharmacological action of masitinib on mast cells and neutrophils may be involved in preventing motoneuron degeneration, contributing to the potential beneficial effect in ALS (Trias et al, 2018).…”
Section: Masitinib a C-kit Receptor Inhibitormentioning
confidence: 79%
See 1 more Smart Citation
“…The observed control of microgliosis and subsequently, the neuroinflammation, together with the significantly prolonged survival of the animals, supported the evaluation of its efficacy in ALS patients (Trias et al, 2016). Moreover, it has been reported that the pharmacological action of masitinib on mast cells and neutrophils may be involved in preventing motoneuron degeneration, contributing to the potential beneficial effect in ALS (Trias et al, 2018).…”
Section: Masitinib a C-kit Receptor Inhibitormentioning
confidence: 79%
“…These inhibitors are ATP‐competitive, selective among different kinases and predicted to be permeable to the CNS according to the in vitro parallel artificial membrane permeability assay (PAMPA) assay. Moreover, the best compounds of this purine family were selected for further studies in vitro and showed that they were able to recover TDP‐43 homeostasis (decreasing TDP‐43 phosphorylation and recovering nuclear localization) in lymphoblasts from ALS and frontotemporal lobar degeneration patients (Vaca et al, 2020). Finally, these inhibitors, including ERP2.37 (Figure 1) were tested in different in vivo models, such C. elegans and TDP‐43 transgenic mice, confirming the same behaviour (Martinez‐Gonzalez, Rojas‐Prats et al, 2019).…”
Section: Protein Kinase Inhibitors In Preclinical Development For Alsmentioning
confidence: 99%
“…We report, here, our results of the treatment of control and sporadic ALS lymphoblasts with Tideglusib, an in-house designed non-ATP competitive GSK-3β inhibitor, that have shown good safety and tolerability in patients with different neurological diseases [23][24][25][26]34]. We have previously demonstrated the usefulness of lymphoblastoid cell lines derived from patients to study TDP-43 homeostasis [27,30] being a suitable platform for preclinical evaluation of potential drug candidates for TDP-43 proteinopathies such as Frontotemporal Dementia (FTD) or ALS [35]. Furthermore, we have shown that by reducing TDP-43 aberrant phosphorylation, we can restore not only TDP-43 homeostasis but also TDP-43 functionality in FTD lymphoblasts [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cell division cycle kinase 7 (CDC7) plays a role in the hyperphosphorylation of TDP-43, a central protein in the pathogenesis of ALS [43]. Notably, CDC7 inhibitors have shown promise in ALS animal and cellular models by reducing TDP43 phosphorylation [44,45]. Furthermore, a small molecule inhibitor of CDC7 reduced TDP-43 phosphorylation and prevented neurodegeneration in TDP-43-transgenic animals [43].…”
Section: Biological and Functional Analyses Of Switch Genesmentioning
confidence: 99%